Additive Manufacturing of Copper-ABS Filament by Fused Deposition Modeling (FDM) / N Sa'ude ...[et al.] - Sa'ude, N; Ibrahim, M; Ibrahim, MHI; Wahab, MS; Haq, R; Marwah, OMF; Khirotdin, RK (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
Highly copper filled in an acrylonitrile butadiene styrene (ABS) matrix will provide a brittles filament in the layered manufacturing process. This paper aims to investigate the optimum composition of metal filler, binder and surfactant material of copper-ABS filament on the melt temperature and federate in layered manufacturing (LM) process. The compounding of copper-ABS feedstock was accomplish by the Brabender Plastograph Mixer in weight percentage (wt.%). The copper-ABS filament was fabricated by single screw extruder machine with different material composition, melting temperature and deposited material on the FDM Machine(Model: Prusa I3) in a layer by a layer processes with appropriate setting on melt temperature and the feed rate. Based on the result obtained, it was found that, increment of 75% copper filled in ABS matrix in weight percentage (wt. %) increase the Melt Flow Rate (MFR) filament in layered manufacturing process. It can be observed that, highest temperature and federate is needed to extrude polymer matrix composite (PMC) wire filament compare to ABS polymer filament material in FDM machine. The deposition of copper-ABS filament on the FDM platform will create a new paradigm on polymer matrix composites material in the Rapid Manufacturing (RM) process